10Be chronology of deglaciation and ice-dammed lake regression in the vicinity of the Mylodon Cave (Cerro Benitez, Patagonia, Chile) - Girault, Igor; Todisco, Dominique; Ciner, Attila; Sarikaya, Mehmet Akif; Ylldlrlm, Cengiz; Quiquerez, Alinelie; Martin, Fabiana Maria; Borrero, Luis; Fabel, Derek; Grandjean, Philippe; Nehme, Carole; Mouralis, Damase (My University, 2022)
Located 51.5 degrees S in the vicinity of the Southern Patagonian Ice Field, Cerro Benitez and the glacial valley of Lago Sofia host several caves and rock shelters that were occupied by megafauna and humans during the Late Pleistocene, including the Mylodon Cave and two of the oldest archaeological sites in Patagonia. During the last glaciation, Cerro Benitez was alternately covered by the Patagonian Ice Sheet and surrounded by an ice-dammed lake which restricted the access to the caves and rock shelters located under its uppermost level, 155 m a.s.l. This study aims to provide a detailed chronology of the deglaciation and lake regression in Cerro Benitez. The glacial fluctuations and the variations of lake level were reconstructed from multi-scale, remote-sensing data and field geomorphological mapping. In addition, we calculated the surface exposure age of 11 erratic blocks located above and on the lacustrine erosional platform using terrestrial cosmogenic Be-10 in order to date ice downwasting and lake regression, respectively. Dates of ice downwasting and lake regression events were modelled from prior surface exposure ages using Bayesian statistics. The results suggest that the Patagonian Ice Sheet locally thinned by at least 300 m during MIS 3 in the aftermath of a major glacial advance. Following deglaciation, the ice-dammed lake experienced a slow local regression (ca. 2.5 mm. a(-1) until 16.9 ka B2k, interpreted as the result of lake basin tilting due to differential post-glacial isostatic rebound. This initial phase of lake regression was followed by a faster regression caused by the reversal of the lake drainage between 16.9 and 15.4 ka B2k. We assess the chronological model by comparison with uplift and lakeshore erosion rates from the literature and eventually discuss the implications for megafaunal colonisation of the area. (C) 2022 Elsevier Ltd. All rights reserved.
Keywords: pleistocene; glaciation; south america; cosmogenic isotopes; geomorphology; glacial; chronological modelling; mylodon cave